Pelaksanaan Model Pendidikan Inklusif di Sekolah Wilayah D.I Yogyakarta - Wartomo Wartomo (Mukaddimah: Jurnal Studi Islam, 2016)
The study is aimed to investigate the implementation of inclusive education model in the region of Yogyakarta. Variables that are revealed in this study include: institutional, learning curriculum and evaluation, workforce, student affairs, infrastructure, and financing. Subjects were teachers, principals and inclusive education committee in the Yogyakarta region. The study population, applied in total population that all Inclusive Schools that are in the research area be a place of research, both public and private Inclusive Schools. This type of research evaluation, initiated the survey, conducted in May-October 2014. The data collection technique using questionnaires; interview; observation, documentation. The data analysis techniques used are integrated or synchronously between quantitative and qualitative descriptive approach. The results of the study visits of several indicators: (1) institutional conditions indicate, schools generally have a manager special fittings permit; (2) curriculum developed in the educational unit adjustment has been made to accommodate the needs of service children with special needs (ABK) in the setting of inclusive education; (3) conditions do not have the energy workforce mostly Teachers Special Advisor (GPK) in charge and appointed specifically as a teacher GPK inclusive schools. (4) the condition of the student; the admission of new students in the school inclusion of DIY presents special quota (special seats) behalf. Conditions student in primary school inclusive of the Province of DIY are: enrollment ABK; (5) facilities and infrastructure; Data shows; special room inclusions 262; (6) financing; most schools have incorporated components of the financing for the implementation of inclusive education programs.